THE POTENTIAL DEVELOPMENT OF BUDDHIST TOURISM: A CASE STUDY OF TEMPLES IN SADOA DISTRICT, SONGKHIA PROVINCE - Kittipanyo (Thammachot), Phrakrit; Noonklam, Direk; Praekpan, Banyat (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were to 1) study the guidelines for developing the potential of Buddhist tourist attractions. in the case of temples in Sadao District, Songkhla Province 2) study the recommendations on the guidelines for developing the potential of Buddhist tourist attractions Use an integrated research methodology. by quantitative research studies, The sample group consisted of 399 tourists who visited the temples in Sadao District. The instruments used for data collection were questionnaires. Data analysis were percentage, mean, and standard deviation. Use a ready-made statistical program to analyze the data. and qualitative research Data were collected through in-depth interviews with 25 key informants/person. The results showed that 1) the potential development of Buddhist tourism in A case study of temples in Sadao District, Songkhla Province, including all 4 aspects, was at a high level (𝑥̅ = 3.86). 2) Recommendations on the development of the potential of Buddhist tourism in all 4 aspects found 1) the potential for attractiveness. tourist make it stand out Selling point for temples in Sadao District Increase the impression of tourists 2) In terms of the potential to support tourism, there must be a cleaning of public utilities. Maintain cleanliness and breakdown of utility commodities The government should come and help to repair and improve roads in the area in front of tourist attractions. Security guards should be provided. 3) The potential of tourism attraction management. The process of preserving tourist attractions should be created to preserve ancient sites or ancient objects to be preserved from generation to generation. 4) In terms of participation potential. Building cooperation by arranging to bring in monks, community leaders, entrepreneurs, and various groups of villagers as committee members. Participate in the care and development of the temple